(3KeGQ GdbdhH aj GdeVGa hGdefShHs - (3CHi efUhQ YHO Gdedc Hf eMeO Hf ESeGYjd GdfjSCHhQis ((3NVQ Hf eMeO s)
(3ChdgG (B:s
(3bhS Gddg , gi GdJi jbGd dgG bhS bRM , hjTHg HgG eG jbGd dHKg hdGjOhe ecKg ceG bGd GdMeGSi (B: (3aTHgJ SQYI CjGege HSQYI bhS jSei bRM s
(3BNQgG (B:s
(3EPG eG ONd GdfGQ Mci QGFMI GdLfI bdJ bO CWdbJ YfGf Gdbde ai GdfbGW aQGFO gPG GdcJGH hhajJ HMeO Gddg hefg HeG hYOJ ef MSf GdGNJUGQ s
(3Cda ddCejQ YHjO Gddg Hf CMeO Hf Ydi Hf ESeGYjd GdejcGdis
(3HChdgG agQSJ HNW MOjKs
(3hgfGc faU ai GdhQbI GdKGdKI BNQ GdHGH GdKGfi hChd GdKGdKs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B221 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B573s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs